Application of digital image correlation system for reliable deformation measurement of concrete structures at high temperatures. (1st August 2019) - Le, Dinh Ba; Tran, Son Duy; Torero, Jose L.; Dao, Vinh T.N.
Highlights: Review of methods for deformation measurement of concrete at elevated temperatures. New test setup using 3D DIC technique with a blue light and a band-pass filter. Theoretical and experimental evidence proving the capability of the novel setup. Potential applications of the new test system. Abstract: Reliable data on concrete deformation at high temperatures are critical to ensure the suitable predictive capability of the models for such important deformation-related properties as stress-strain relations, modulus of elasticity and load-induced thermal strains. This paper first reviews currently available technologies for measuring the deformation of concrete at high temperatures and the relevant major experiments. It is shown that such deformation has usually been determined either indirectly or outside the heated zones, thereby resulting in uncertainties that are difficult to be properly quantified. Key details of a newly-developed test setup using an optimised 3D digital image correlation technique, a radiant heating facility and an optical system with a blue illumination and a band-pass filter are then reported. It is shown via both theoretical and experimental evidence that the new system allows to successfully overcome the challenges related to thermal radiation, contrast of image, stability of speckle pattern and presence of hot air; thereby proving the reliability and capability of this innovative setup. Finally, several key potential applications of the new system are suggested.